Localized release of matrix metallopeptidase 8 in fatal cerebral malaria - Georgiadou,A; Naidu,P; Walsh,S; Kamiza,S; Barrera,V; Harding,SP; Moxon,CA; Cunnington,AJ (Clinical & Translational Immunology, 2021)
ObjectiveCerebral malaria (CM) is a complication of Plasmodium falciparum malaria, in which progressive brain swelling is associated with sequestration of parasites and impaired barrier function of the cerebral microvascular endothelium. To test the hypothesis that localised release of matrix metallopeptidase 8 (MMP8) within the retina is implicated in microvascular leak in CM, we examined its expression and association with extravascular fibrinogen leak in a case–control study of postmortem retinal samples from 13 Malawian children who met the clinical case definition of CM during life. Cases were seven children who were found on postmortem examination to have ‘trueCM’ (parasite sequestration in brain blood vessels), whilst controls were six children who had alternative causes of death (‘fauxCM’, no parasite sequestration in blood vessels).MethodsWe used immunofluorescence microscopy and independent scoring, by two assessors blinded to the CM status, to assess MMP8 expression, extravascular fibrinogen as an indicator of vascular leak and their colocalisation in the retinal microvasculature.ResultsIn ‘trueCM’ subjects, MMP8 staining was invariably associated with sequestered parasites and a median of 88% (IQR = 74–91%) of capillaries showed MMP8 staining, compared with 14% (IQR = 3.8–24%) in ‘fauxCM’ (Pvalue = 0.001). 41% (IQR = 28–49%) of capillaries in ‘trueCM’ subjects showed colocalisation of extravascular fibrinogen leak and MMP8 staining, compared with 1.8% of capillaries in ‘fauxCM’ (IQR = 0–3.9%, Pvalue = 0.01). Vascular leak was rare in the absence of MMP8 staining.ConclusionMatrix metallopeptidase 8 was extensively expressed in retinal capillaries of Malawian children with malarial retinopathy and strongly associated with vascular leak. Our findings implicate MMP8 as a cause of the vascular endothelial barrier disruption in CM, which may precip